2009
DOI: 10.1111/j.1755-3768.2009.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between central corneal thickness and optic disc size in patients with primary open-angle glaucoma in a hospital-based population

Abstract: . Purpose:  To investigate the relationship between central corneal thickness (CCT) and optic disc size in patients with primary open‐angle glaucoma (POAG) in a hospital‐based population. Methods:  Data for the right eyes of 1435 White patients with POAG were included in a retrospective hospital‐based study. All eyes underwent optic nerve head imaging using Heidelberg Retina Tomograph II (HRT II; Heidelberg Engineering, Heidelberg, Germany) and CCT measurement by ultrasound corneal pachymetry. Eyes with prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, in other population-based studies there was no significant relationship with any optic disc parameter [15,59]. Some hospital-based studies have found CCT associated with optic disc area [60][61][62], nasal rim area [63], as well as no significant correlation of CCT and disc size [62].…”
Section: Biological Factorsmentioning
confidence: 82%
“…However, in other population-based studies there was no significant relationship with any optic disc parameter [15,59]. Some hospital-based studies have found CCT associated with optic disc area [60][61][62], nasal rim area [63], as well as no significant correlation of CCT and disc size [62].…”
Section: Biological Factorsmentioning
confidence: 82%
“…Several studies have assessed the relationship between the CCT and objectively measured optic disc parameters, but they provide inconsistent results. Using the confocal scanning laser ophthalmoscopy (Heidelberg Retina Tomograph, Heidelberg Engineering, Heidelberg, Germany), several hospital-based studies of patients with glaucoma have suggested that the CCT is correlated with the optic disc area and nasal rim volume [57], while another population-based study [58] did not identify these correlations. In another population-based survey [59], no significant relationship was found between the CCT and ONH parameters obtained with retinal tomography.…”
Section: Cornea Lamina Cribrosa and Glaucomamentioning
confidence: 99%
“…[57][58][59][60][61] In particular, a correlation between thinner CCT and larger optic discs seems to be present in POAG patients. 62,63 Larger optic disc diameters may be associated with increased vulnerability to pressure-induced deformation. Therefore, eyes with thinner corneas are more susceptible to glaucomatous damage in comparison with those having thicker corneas.…”
Section: Discussionmentioning
confidence: 99%